DegQ is an important policing link between quorum sensing and regulated adaptative traits in Bacillus subtilis - Tjaša Danevčič; Mihael Spacapan; Anna Dragoš; Ákos T. Kovács; Ines Mandic-Mulec (Microbiology Spectrum, 2023)
ABSTRACT Quorum sensing (QS) is a widespread bacterial communication system that controls important adaptive traits in a cell density-dependent manner. However, mechanisms by which QS-regulated traits are linked within the cell and mechanisms by which these links affect adaptation are not well understood. In this study, Bacillus subtilis was used as a model bacterium to investigate the link between the ComQXPA QS system, DegQ, surfactin and protease production in planktonic and biofilm cultures. The work tests two alternative hypotheses predicting that hypersensitivity of the QS signal-deficient mutant (comQ::kan) to exogenously added ComX, resulting in increased surfactin production, is linked to an additional genetic locus, or alternatively, to overexpression of the ComX receptor ComP. Results are in agreement with the first hypothesis and show that the P srfAA hypersensitivity of the comQ::kan mutant is linked to a 168 strain-specific mutation in the P degQ region. Hence, the markerless ΔcomQ mutant lacking this mutation is not overresponsive to ComX. Such hyper-responsiveness is specific for the P srfAA and not detected in another ComX-regulated promoter, the P aprE , which is under the positive control by DegQ. Our results suggest that DegQ by exerting differential effect on P srfAA and P aprE acts as a policing mechanism and the intracellular link, which guards the cell from an overinvestment into surfactin production. IMPORTANCE DegQ levels are known to regulate surfactin synthesis and extracellular protease production, and DegQ is under the control of the ComX-dependent QS. DegQ also serves as an important policing link between these QS-regulated processes, preventing overinvestment in these costly processes. This work highlights the importance of DegQ, which acts as the intracellular link between ComX production and the response by regulating extracellular degradative enzyme synthesis and surfactin production.